Developing a sustainable platform for open access publishing in Armenia - Zargaryan, Tatev; Landoy, Ane; Repanovici, Angela (Qualitative and Quantitative Methods in Libraries, 2020)
In 2017 two Armenian universities with the support of the University of Bergen teamed up within the project called “Developing a sustainable platform for open access publishing in Armenia”. The project started with a survey regarding attitudes and barriers of academic staff in Armenian universities to open access and institutional repositories. This article will present the analysis of the OA survey results conducted with American University of Armenia and Public Administration Academy of the Republic of Armenia. The article will be concluded with the recommendations on the developed IR guidelines, specify acquisition models taking into consideration the survey results.